A Simple LC/MS/MS Method for the Determination of Moxifloxacin N-Sulfate in Rat Plasma and Its Application in a Pharmacokinetic Study. (27th November 2019) - Li, Jian; Yuan, Yin; Fan, Rong; Su, Qinghong; Wang, Siyuan; Zhou, Tianyan; Lu, Wei
Abstract: Moxifloxacin N-sulfate is one of the main metabolites of moxifloxacin in phase II metabolism mediated by sulfotransferases. In this study, a simple, rapid, and sensitive LC/MS/MS method with one-step protein precipitation with methanol was developed and validated to quantify the concentration of moxifloxacin N-sulfate in rat plasma. The chromatographic separation was accomplished by using an Agilent Extend C18 column (4.6 × 250 mm; 5 μm) with a mobile phase consisting of acetonitrile and distilled water (30:70, v/v) containing 5 mM ammonium formate (pH = 8.82 adjusted by ammonia) at a flow rate of 1.0 mL/min. A triple quadrupole tandem mass spectrometer with electrospray ionization source was used as a detector operated by multiple reaction monitoring in the negative-ion mode with m/z 480.2/436.3. The calibration curve was linear ranging from 2 to 200 ng/mL. The intraday and interday precision values (RSD) were less than 7.10%, and the intraday and interday accuracy values (relative error) were within –0.40 to 4.99%. Stabilities of all QC samples were within general assay acceptability criteria according to the U.S. Food and Drug Administration guidelines. No considerable matrix effect was found. A pharmacokinetic study of moxifloxacin N-sulfate after a single oral dose of moxifloxacin in rats was carried out using this new method.